2000
DOI: 10.1177/000331970005100607
|View full text |Cite
|
Sign up to set email alerts
|

Increased QT Interval Dispersion After Hemodialysis: Role of Peridialytic Electrolyte Gradients

Abstract: Chronic renal failure patients on maintenance hemodialysis (HD) have a number of ECG abnormalities and cardiac arrhythmias. Clinical and experimental data have shown that increased QT dispersion is associated with severe ventricular arrhythmias and sudden cardiac death. Therefore, the aim of this study was to investigate whether the uremic patients receiving long-term HD have increased QTc interval and/or QTc dispersion compared to normal subjects and to evaluate the effect of electrolyte changes between the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 22 publications
4
57
1
Order By: Relevance
“…Although various factors such as the middle molecules have been implicated, the most frequent cause of arrhythmias appears to be related to changes in fluid status and electrolytes, particularly potassium. 11,50 The most convincing evidence for the role of dialysis in SCD comes from a temporal relationship between the days of dialysis and SCD 3 ( Figure 3). It is well-known that the rate of SCD in center-based, intermittent hemodialysis is greatest during the first 12 hours of starting dialysis and the last 12 hours of the 72-hour dialysis-free interval.…”
Section: Dialysis Disequilibrium As a Trigger For Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various factors such as the middle molecules have been implicated, the most frequent cause of arrhythmias appears to be related to changes in fluid status and electrolytes, particularly potassium. 11,50 The most convincing evidence for the role of dialysis in SCD comes from a temporal relationship between the days of dialysis and SCD 3 ( Figure 3). It is well-known that the rate of SCD in center-based, intermittent hemodialysis is greatest during the first 12 hours of starting dialysis and the last 12 hours of the 72-hour dialysis-free interval.…”
Section: Dialysis Disequilibrium As a Trigger For Arrhythmiasmentioning
confidence: 99%
“…10 Significant sudden shifts in electrolytes and fluid volume that surrounds a dialysis session acts as a trigger and can initiate life-threatening arrhythmias in patients with a susceptible substrate. 11 Hence, it is conceivable that risk assessment tests that evaluate these variables could be used to identify dialysis patients at risk of SCD. In this review, we discuss the rationale behind the use of specific risk assessments to evaluate the risk of SCD in the dialysis cohort and review the current evidence on the use of some of these tests in dialysis patients with ESRD.…”
mentioning
confidence: 99%
“…Clinical and experimental data have shown that increased QT dispersion (QTd) is associated with severe ventricular arrhythmias and sudden cardiac death. [8][9][10] QT dispersion (QTc max -QT min ) reflects heterogeneity of cardiac repolarization, and increased dispersion is known to predispose the heart to ventricular arrhythmias and sudden cardiac death. 11 Thus, screening of cardiac disease is recommended to prevent cardiovascular death after renal transplant.…”
Section: Introductionmentioning
confidence: 99%
“…QT dispersion (maximum minus minimum QTc interval on a standard 12-lead electrocardiogram) is also taken as a risk factor for ventricular arrhythmias and sudden death [12]. Several authors have reported an acute increase in both QTc and QT dispersion during haemodialysis [17,24]. Although this would support the increase in sudden death related to the dialysis procedure, there are relatively few data showing a direct link between increased QTc or QT dispersion induced by dialysis and either arrhythmia or sudden death [21].…”
Section: Discussionmentioning
confidence: 99%